2010
DOI: 10.1186/1471-2180-10-85
|View full text |Cite
|
Sign up to set email alerts
|

Environmental distribution of prokaryotic taxa

Abstract: BackgroundThe increasing availability of gene sequences of prokaryotic species in samples extracted from all kind of locations allows addressing the study of the influence of environmental patterns in prokaryotic biodiversity. We present a comprehensive study to address the potential existence of environmental preferences of prokaryotic taxa and the commonness of the specialist and generalist strategies. We also assessed the most significant environmental factors shaping the environmental distribution of taxa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
121
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 45 publications
16
121
0
1
Order By: Relevance
“…Spatial differentiation among samples was highly correlated with salinity, confirming the observations of two global meta-analyses of microbial diversity based on 16S rRNA gene sequences (Lozupone and Knight, 2007;Tamames et al, 2010). In one of these studies, Lozupone and Knight (2007) found that salinity was the primary environmental determinant for community composition across marine, freshwater, sediment and soil environments, more so than temperature, pH or other environmental factors.…”
Section: Discussionsupporting
confidence: 65%
“…Spatial differentiation among samples was highly correlated with salinity, confirming the observations of two global meta-analyses of microbial diversity based on 16S rRNA gene sequences (Lozupone and Knight, 2007;Tamames et al, 2010). In one of these studies, Lozupone and Knight (2007) found that salinity was the primary environmental determinant for community composition across marine, freshwater, sediment and soil environments, more so than temperature, pH or other environmental factors.…”
Section: Discussionsupporting
confidence: 65%
“…Timoner et al (2014a) observed that biofilm on coarse sand, cobbles and hyporheic sediment reacted differently to the rewetting. OTUs affiliated to Actinobacteria and Proteobacteria were abundant in epipsammic and hyporheic biofilms, similarly to what is occurring in soils and river sediments (Gao et al, 2005;Tamames et al, 2010), while OTUs affiliated to the Cyanobacteria and the Firmicutes predominated on cobbles. These changes in community composition were accompanied by an increase in richness and diversity in epipsammic and hyporheic biofilms, likely favored by the increased number of niches provided by sand particles (Sigee, 2005).…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 77%
“…External osmolarity is the major factor shaping microbial community composition (Lozupone and Knight, 2007;Tamames et al, 2010), as both hyperand hypo-osmotic environmental changes constitute a major stress for single cell organisms (Morbach and Krämer, 2002). Moreover, primary productivity has also been shown to influence the diversity and composition of bacterial communities (HornerDevine et al, 2003;Smith, 2007).…”
Section: Discussionmentioning
confidence: 99%